Palm oil based alkyd/polyaniline as electrically conductive coating with UV curing ability / Siti Nur Amalina Ramlan - Siti Nur Amalina , Ramlan (2018)
Environmentally friendly products are gaining popularity recently, in line with the increasing global demand for green technology. Ultraviolet (UV)-curable coating is one of them since it involves minimal, if any, emission of volatile organic compounds during the curing process. Besides, UV curing technology enables coatings to be cured within much shorter time compared to thermal curing process. The aim of this study is to produce electrically conductive UV-curable coating which is environmentally friendly. Polyaniline is a polymer with excellent electrical conductivity and it is known to exhibit anti-corrosion properties through passivation. However, polyaniline itself is not a good coating binder, as it tends to produce brittle film with poor adhesion. Therefore, in this work palm oil-based polyester binder was synthesized and blended with polyaniline to produce electrically active coating with improved film properties. The alkyd resin was formulated with considerable amount of maleic acid formulation in order to render it UV-curable. Both alkyd and polyaniline was characterized using FTIR, 1H-NMR, TGA and UV-Vis. Some of the tests carried out to investigate the film properties of the coatings include pencil hardness test, adhesion tape test, water and chemical resistant test, conductivity, and thermal stability. Alkyd has improved poor coating binder properties of polyaniline in term of their mechanical properties. In addition, anticorrosion property of the coatings on mild steels were determined using open circuit potential (OCP) values, Tafel analysis and electrochemical impedance spectroscopy (EIS). Alkyd coating which contains 0.5% polyaniline shows improved corrosion resistance properties with corrosion rate 2.277 x 10-5 mm/y. A stable and homogeneous alkyd/polyaniline coating film has been prepared in this project with evidences from the FTIR analyses and conductivity studies showing strong interaction between alkyd and polyaniline through crosslinking reaction.